2022
DOI: 10.3390/ph15020253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultramicronized Palmitoylethanolamide (um-PEA) in COVID-19 Early Stages: A Case–Control Study

Abstract: Ultramicronized palmitoylethanolamide (um-PEA), a compound with antioxidant, anti-inflammatory and neuroprotective properties, appears to be a potential adjuvant treatment for early stages of Coronavirus disease 2019 (COVID-19). In our study, we enrolled 90 patients with confirmed diagnosis of COVID-19 that were randomized into two groups, homogeneous for age, gender and BMI. The first group received oral supplementation based on um-PEA at a dose of 1800 mg/day for a total of 28 days; the second group was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…PEA and LUT have potent neuroprotective and anti-inflammatory properties, and their bioavailability is significantly improved when administered in a micronized versus non-micronized form [ 22 ]. Ultra-micronization reduces particle size, improving absorption, metabolism, and therapeutic efficacy, as evidenced by several clinical studies [ 2 , 11 , 12 , 22 ]. PEA-LUT microgranules can be sublingually administered, which further enhances efficacy by minimizing the loss of activity from gastrointestinal degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEA and LUT have potent neuroprotective and anti-inflammatory properties, and their bioavailability is significantly improved when administered in a micronized versus non-micronized form [ 22 ]. Ultra-micronization reduces particle size, improving absorption, metabolism, and therapeutic efficacy, as evidenced by several clinical studies [ 2 , 11 , 12 , 22 ]. PEA-LUT microgranules can be sublingually administered, which further enhances efficacy by minimizing the loss of activity from gastrointestinal degradation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding, which is consistent with the neuroinflammatory hypothesis of long COVID symptoms [ 9 ], provides a rationale for targeting neuroinflammation to promote recovery. Palmitoylethanolamide and luteolin (PEA-LUT) have anti-inflammatory and neuroprotective properties [ 10 , 11 , 12 ]. In the present study, we investigated whether treatment with PEA-LUT, with or without olfactory training, was associated with an improvement in measures of olfactory function and mental clouding among patients affected by long COVID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 ARDS is the clinical equivalent of diffuse alveolar damage, a histopathological picture consistently found in patients who died from severe COVID-19. 13 One us (LR) was among the first in the international medical literature to propose the use of PEA in COVID-19 and long-COVID 37 ; subsequently, further research supported this rationale, [38][39][40] and revealed also its utility in inhibiting the Nod-like receptor family pyrin domain containing 3 inflammasome expression in cultured murine alveolar macrophages stressed by the spike protein of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 41 as well as in inhibiting the entry of SARS-CoV-2, the etiological agent of COVID-19, into human cell lines by interacting with the spike protein and the angiotensin converting enzyme 2 receptors. 42 Moreover, the use of PEA in combination with luteolin improved olfactory dysfunction or mental clouding in a cohort of 69 patients (43 women, 26 men) with a mean age of 40.6 years affected by long-COVID, 43 and normalized γ-aminobutyric acid B -ergic activity and cortical plasticity in a further cohort of 39 long-COVID patients (26 women, 13 men) with a mean age of 49.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors showed the efficacy of umPEA-LUT to fight the inflammation caused by COVID-19 infection [ 13 , 14 , 15 ], as well as the ability of the molecule of inhibiting the penetration of the SARS-CoV-2 virus protecting people from the infection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%